Promoting innovation in the Mediterranean. Profiles and expectations of business incubators, technology parks and technology transfer offices - Dagault S.; Ziane-Cherif A.; Menéndez A. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
Developing innovation economies is even more important during a crisis and this is why virtually every country in the world is striving to remain competitive. Their aim is to generate added value and create sustainable jobs. The development priorities for all countries, and in particular for the MED countries include developing promising new industrial activities in various areas of excellence, encouraging entrepreneurship and pushing forward future economic leaders, attracting foreign investment in high-end business areas and ensuring that technology parks and innovation showcases play a role in knowledge exchanges. Yet in response to these challenges, several countries in the Mediterranean region are falling behind at different levels. They find it difficult to acquire sufficient critical mass for investments and installations. They also lack global visibility and perform poorly when commercialising research results and public-private partnerships are difficult to establish. The study entitled Promoting Innovation in the Mediterranean is the result of field work, a survey of existing programmes and various workshops conducted alongside the “players of change in the Mediterranean”. It takes stock of current innovative ecosystems that are being developed in the Southern Mediterranean region. Three types of innovation support structures are targeted: technology parks, business incubators and technology transfer offices. The 7 MED countries concerned include: Algeria, Egypt, Jordan, Lebanon, Morocco, Palestine and Tunisia. The study is not simply an analysis of macro-economic issue; it identifies the key elements required to drive new innovation dynamics across the Mediterranean. They include the promotion of best practises, the need to identify and involve industry leaders as well as networking between communities and innovation clusters at regional level.